The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.vetpar.2010.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toxoplasma gondii and Neospora caninum infections in sheep from Uberlândia, Minas Gerais State, Brazil, by different serological methods

Abstract: Toxoplasmosis and neosporosis have been recognized as economically important diseases with considerable impact on the livestock industry. Considering the scarce information on the occurrence of Toxoplasma gondii and Neospora caninum infections in sheep from Uberlândia, Minas Gerais State, Brazil, this study aimed to investigate the frequency of antibodies against these parasites in sheep sera from this region by using different serological methods. A total of 155 sheep serum samples were analyzed by the indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
1
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 63 publications
6
28
1
12
Order By: Relevance
“…The prevalence of N. caninum infection observed in this study (7%) was similar to results from other surveys conducted in Brazil (FIGLIUOLO et al, 2004;ROMANELLI et al, 2007;UENO et al, 2009;SALABERRY et al, 2010;MUNHOZ et al, 2010;FARIA et al, 2010;MACHADO et al, 2011;ANDRADE et al, 2012) and in other countries, such as China (HUI, 2008), Czech Republic (BARTOVA et al, 2009 and Spain (PANADERO et al, 2010), with reported seropositivity rates for N. caninum ranging from 8.0 to 13.91% in the sheep samples analyzed using ELISA or IFAT. An association between the prevalence of N. caninum and crossbreed animals (P=0.0249) was observed.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The prevalence of N. caninum infection observed in this study (7%) was similar to results from other surveys conducted in Brazil (FIGLIUOLO et al, 2004;ROMANELLI et al, 2007;UENO et al, 2009;SALABERRY et al, 2010;MUNHOZ et al, 2010;FARIA et al, 2010;MACHADO et al, 2011;ANDRADE et al, 2012) and in other countries, such as China (HUI, 2008), Czech Republic (BARTOVA et al, 2009 and Spain (PANADERO et al, 2010), with reported seropositivity rates for N. caninum ranging from 8.0 to 13.91% in the sheep samples analyzed using ELISA or IFAT. An association between the prevalence of N. caninum and crossbreed animals (P=0.0249) was observed.…”
Section: Resultssupporting
confidence: 92%
“…In these properties, animal management is more appropriate, reducing the contact with sources of N. caninum infection. However, Salaberry et al (2010) found no correlation between breed and N. caninum infection and Nasir et al (2012), on the contrary, found higher infection prevalence in purebred animals. ¹ Relationship between the total number of positive animals per variable and the total number of animals from each variable.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Risk factors such as age, contact with cats, breeding system, and water supply can be highlighted and have been previously identified in ovine toxoplasmosis in Brazil (ROMANELLI et al, 2007;PINHEIRO et al, 2009;LOPES et al, 2010;ROSSI et al, 2011). Considering the importance of toxoplasmosis and the lack of epidemiological information in the state of Bahia, the aims of this study were to determine the prevalence of T. gondii infection in sheep flocks from southern Bahia state and identify possible risk factors associated with the infection.…”
Section: Introductionmentioning
confidence: 99%
“…Although comparison of frequencies of infection between regions are difficult, differences could be due to sampling methods employed herein. Rossi et al (2011), in a study of neosporosis using different serological methods, suggest that variations among frequencies rate may also be due to differential environment contamination and climatic conditions. Indeed, regions that present high annual rainfall index, such as Rondônia state, present higher occurrence rate for N. caninum.…”
Section: Discussionmentioning
confidence: 99%